A Labor Capital Asset Pricing Model. (5th June 2017) - KUEHN, LARS‐ALEXANDER; SIMUTIN, MIKHAIL; WANG, JESSIE JIAXU
ABSTRACT: We show that labor search frictions are an important determinant of the cross‐section of equity returns. Empirically, we find that firms with low loadings on labor market tightness outperform firms with high loadings by 6% annually. We propose a partial equilibrium labor market model in which heterogeneous firms make dynamic employment decisions under labor search frictions. In the model, loadings on labor market tightness proxy for priced time‐variation in the efficiency of the aggregate matching technology. Firms with low loadings are more exposed to adverse matching efficiency shocks and require higher expected stock returns.